Patient satisfaction towards the quality of nursing care among the patients of private hospitals of Jodhpur, India - Parihar, Raju Ram; Suthar , Anju (International Journal of Research in Medical Sciences, 2023)
Background: Patient satisfaction is a good indicator for measuring the quality of nursing care delivered by a nurse to a hospitalized patient. This will help the nursing administrator to identify ways of improving nursing and health care services. The study aims to assess the level of patient’s satisfaction towards quality of nursing care among the patients. Methods: A descriptive survey study was carried on 100 patients selected using non-probability purposive sampling, who were discharged from the selected private hospitals at Jodhpur, Rajasthan. A Modified form of Dr. Laschinger’s “Patient Satisfaction with Nursing Care Quality Questionnaire” (PSNCQQ) was used to measure patient satisfaction. A written permission was obtained to conduct study from the authority and an informed consent was taken from each participant. Results: The study findings indicate that majority (70%) of the sample were highly satisfied with nursing care with mean patient satisfaction score 61.38±9.692 (76.72%). Majority (66%) patients were satisfied with “Information given regarding investigations and treatments” and only (26%) were satisfied with “Coordination of care after discharge.” Patients aged 18-30 years, belonged to urban area, up to secondary educated and admitted through OPD were found more satisfied. Conclusions: The study showed that majority of the participants were highly satisfied with quality of nursing care provided in private hospital. The PSNCQQ is a useful instrument for evaluating and improving nursing care. The nurse administrator can contribute to quality service provision by evaluating patient satisfaction to develop and improve nursing care based on patients' expectations.